Analysis of Fraud Hexagon Dimensions and Their Effect on Financial Reporting Fraud Using the Beneish M-Score: Evidence from Infrastructure Companies Listed on the IDX (2020–2024) - Melani Purnama; Hardiyanto, Arief Tri; Indrayono, Yohanes (International Journal Administration, Business & Organization, 2025)
Financial statement fraud poses a major risk to stakeholders as it obscures a firm’s true financial condition, disrupts market efficiency, and weakens corporate governance. This study investigates the determinants of financial statement fraud in Indonesian infrastructure firms listed on the stock exchange by applying the Fraud Hexagon framework, comprising pressure, opportunity, rationalization, capability, ego, and collusion, while incorporating political connections and discretionary accruals as additional factors. Using a quantitative approach with logistic regression on panel data from 2020–2024, the results show that external pressure, financial performance targets, weak monitoring, market outcomes, and political ties significantly increase the likelihood of fraudulent financial reporting. Discretionary accruals also demonstrate a strong association with fraud, indicating managers’ opportunistic earnings manipulation. The findings empirically support the extended Fraud Hexagon framework in the Indonesian context and highlight the reinforcing role of political connections in unethical financial behavior. This study contributes to theory and practice by offering insights for regulators, auditors, and policymakers to strengthen fraud detection and prevention mechanisms.